2021
DOI: 10.3389/fpubh.2021.692402
|View full text |Cite
|
Sign up to set email alerts
|

Community Violence Exposure and School Functioning in Youth: Cross-Country and Gender Perspectives

Abstract: Background: Many children and adolescents experience violent events which can be associated with negative consequences for their development, mental health, school, and social functioning. However, findings between settings and on the role of gender have been inconsistent. This study aimed to investigate cross-country and gender differences in the relationship between community violence exposure (CVE) and school functioning in a sample of youths from three countries.Methods: A self-report survey was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 69 publications
0
8
0
1
Order By: Relevance
“…We also examined the extent to which sex predicted subgroup membership. Several studies have found differences in rates of community violence exposure between boys and girls (e.g., Finkelhor et al, 2015 ; Javdani et al, 2014 ; Koposov et al, 2021 ). However, because studies are inconsistent in their findings these analyses were considered exploratory.…”
Section: Introductionmentioning
confidence: 99%
“…We also examined the extent to which sex predicted subgroup membership. Several studies have found differences in rates of community violence exposure between boys and girls (e.g., Finkelhor et al, 2015 ; Javdani et al, 2014 ; Koposov et al, 2021 ). However, because studies are inconsistent in their findings these analyses were considered exploratory.…”
Section: Introductionmentioning
confidence: 99%
“…Negative consequences of violence include academic difficulty, low self-esteem, school avoidance, depression, and anxiety ( Lester et al, 2017 ). An in-depth and comprehensive study on the prevention of violence in schools is both urgent and necessary ( Koposov et al, 2021 ). Victims of school violence are more anxious and insecure than their peers, and their reaction is to cry and isolate themselves ( Wijayaratne, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the relevant literature and content of the items, we hypothesized that (1) there would be two dimensions: witnessing and victimization. A series of recent studies have indicated that exposure to community violence can adversely affect individual development and health outcomes, including mental health problems, social relationships, and cognitive functioning (Brady, 2006; Castellví et al, 2017; Koposov et al, 2021). Therefore, given strong and consistent associations between community violence and social and individual functioning, we hypothesized that (2) exposure to community violence would be associated with greater mental health problems, negative relationship quality with spouse/partner, and traumatic life events.…”
Section: Introductionmentioning
confidence: 99%